A Survey on the Knowledge and Attitude of Iranian Endodontists toward Evidence Based Dentistry in 2017 - Mousavi, Seyed Amir; Khademi, Abbasali; Shahnaseri, Shirin; Vakili, Mahan; Bagherieh, Shervin (Journal of Dental School, 2020)
Objectives Dentists make clinical decisions about dental cares on a daily basis. Thus, the best scientific evidence should be used to maximize the probability of successful patient care outcomes. The aim of this study was to evaluate the knowledge and attitude of endodontists towards evidence-based dentistry in Iran in 2017. Methods First a questionnaire was designed by the researchers. To evaluate the quality of the questionnaire, it was sent to six experts and they were asked to comment on each question. After collecting the questionnaires via e-mail, for each question, the statistics were determined by the expert and the reliability of the questionnaire was determined using the Cronbach’s alpha coefficient. The target population of this cross-sectional study was the Iranian endodontists. Data were analyzed by SPSS software, and the frequency and descriptive indexes were used to evaluate the study variables (α=0.05). Results The mean score of knowledge of endodontists about evidence-based dentistry was 63.43±13.7 (out of 100) and the mean score of their attitude towards evidence-based dentistry was 62.22±18.5. Conclusion The results of this study revealed low level of knowledge and attitude of endodontists towards evidence-based dentistry, which is consistent with the results of studies conducted in other countries.